1989
DOI: 10.1093/geront/29.6.808
|View full text |Cite
|
Sign up to set email alerts
|

Concordance Between Physicians and Their Older and Younger Patients in the Primary Care Medical Encounter

Abstract: To test the hypothesis that less concordance exists between older patients and their physicians than between younger patients and their physicians, we examined agreements between physicians and patients on the major goals and topics discussed during an outpatient medical encounter. Using coded audiotapes of the medical visit, patient postvisit interviews, and physician questionnaires, concordance was found to be significantly greater for younger patients and their physicians than for older patients and their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 0 publications
2
38
1
Order By: Relevance
“…An ecological approach is unique to traditional approaches to the study of communication in medical encounters. For example, some studies take a 'single factor' approach by examining the influence of one variable such as gender (Hall & Roter, 1998) or age (Greene, Adelman, Charon & Friedmann, 1989) on physician-patient encounters. However, the influence of any one variable (e.g., ethnicity) may vary depending on the presence of other factors (e.g., the patient's level of education, the physicians' communication style).…”
Section: Conceptual Framework: An Ecological Approachmentioning
confidence: 99%
“…An ecological approach is unique to traditional approaches to the study of communication in medical encounters. For example, some studies take a 'single factor' approach by examining the influence of one variable such as gender (Hall & Roter, 1998) or age (Greene, Adelman, Charon & Friedmann, 1989) on physician-patient encounters. However, the influence of any one variable (e.g., ethnicity) may vary depending on the presence of other factors (e.g., the patient's level of education, the physicians' communication style).…”
Section: Conceptual Framework: An Ecological Approachmentioning
confidence: 99%
“…For instance, it is possible that younger women were more assertive and initiated discussion and requested cancer screening more often than did older women, who were more likely to be passive and modest. 33,34 Future qualitative research is needed to confirm this hypothesis and disentangle the dynamic physician-patient communication process.…”
Section: Factors Associated With Physicians' Cancer Screening Recommementioning
confidence: 99%
“…[3][4][5][6][7] Differences may stem from many factors, including greater numbers of problems treated, 4 poorer health status among older patients, 5 and different preferences for content of interaction. 8 Greene and her colleagues 7 identified lower levels of psychosocial content in the visits of older patients and found that older patients agree with their primary care physician about the purpose of the visit less than do younger patients.…”
mentioning
confidence: 99%
“…8 Greene and her colleagues 7 identified lower levels of psychosocial content in the visits of older patients and found that older patients agree with their primary care physician about the purpose of the visit less than do younger patients. 6 It is not clear whether the different content occurs because of different preferences on the part of older patients or reflects different approaches to care by physicians when facing older patients. Regardless, older patients generally report higher satisfaction with care than their younger counterparts.…”
mentioning
confidence: 99%